2018
DOI: 10.1016/j.jhazmat.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of carbamazepine in plant roots and endophytic rhizobacteria isolated from Phragmites australis

Abstract: Carbamazepine (CBZ) is a pharmaceutical frequently categorized as a recalcitrant pollutant in the aquatic environment. Endophytic bacteria previously isolated from reed plants have shown the ability to promote growth of their host and to contribute to CBZ metabolism. In this work, a horseradish (Armoracia rusticana) hairy root (HR) culture has been used as a plant model to study the interactions between roots and endophytic bacteria in response to CBZ exposure. HRs could remove up to 5% of the initial CBZ conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 42 publications
(47 reference statements)
1
24
0
2
Order By: Relevance
“…Carbamazepine and trimethoprim demonstrated high stability in an in vitro study, where their concentration remained nearly unchanged in carrot cell cultures during the 90 h of exposure, and < 5% of carbamazepine was transformed after 22 days of incubation (Wu et al, 2016). In another lately in vitro study, about 5% of carbamazepine was transformed in horseradish hairy root cell cultures after 6 days of exposure (Sauvêtre et al, 2018). Sulfamethoxazole, sulfadiazine, acetaminophen, oxytetracycline, triclosan, estrone and 17 -estradiol manifested a rapid metabolism with the recovered amount of < 34.0% of the initially spiked dosage.…”
Section: Metabolism Of Pharmaceuticals In Radish Enzyme Extractsmentioning
confidence: 95%
See 1 more Smart Citation
“…Carbamazepine and trimethoprim demonstrated high stability in an in vitro study, where their concentration remained nearly unchanged in carrot cell cultures during the 90 h of exposure, and < 5% of carbamazepine was transformed after 22 days of incubation (Wu et al, 2016). In another lately in vitro study, about 5% of carbamazepine was transformed in horseradish hairy root cell cultures after 6 days of exposure (Sauvêtre et al, 2018). Sulfamethoxazole, sulfadiazine, acetaminophen, oxytetracycline, triclosan, estrone and 17 -estradiol manifested a rapid metabolism with the recovered amount of < 34.0% of the initially spiked dosage.…”
Section: Metabolism Of Pharmaceuticals In Radish Enzyme Extractsmentioning
confidence: 95%
“…In another study, three major metabolites of benzotriazole were found to be >1.5 times more than benzotriazole after 8-day exposure in hydroponic Arabidopsis (LeFevre et al, 2015). Besides the intact plants, the metabolism of pharmaceuticals was also studied using plant cell cultures (Fu et al, 2017;Huber et al, 2009;Macherius et al, 2012;Marsik et al, 2017;Sauvêtre et al, 2018;Wu et al, 2016). Triclosan, naproxen, diclofenac, ibuprofen, gemfibrozil, sulfamethoxazole and atorvastatin were found to rapidly disappeared in carrot cell cultures with 0.4 to 47.3% remaining after 90 h of exposure (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Then, OC was added to this list due to its occurrence in coastal sediments (Combi et al, 2016;Mitchelmore et al, 2019). ECs were added independently at 100 μM final concentration (corresponding to 25, 25, 28, 36 and 24 ppm, respectively) according previous experiments (Vallecillos et al, 2017;Balk and Ford, 1999;König et al, 2016;Sauvêtre et al, 2018). These ECs have low solubility in water (Table 1), and they were added first into the tube with organic solvent (EtOAc, or methanol for CBZ) and evaporated at ambient temperature, under microbiological safety cabinet (MSC).…”
Section: Enrichment Experiments In Liquid Mediummentioning
confidence: 99%
“…Bacteria dwelling within higher plants are adapted to the specific environment of the host plant (Chen et al 2017;Sauvêtre et al 2018). Such endophytic strains have been reported to produce chemicals which can help plant growth (Iqbal et al 2018), resistance to various diseases as well as useful in phytoremediation (Blain et al 2017).…”
Section: Introductionmentioning
confidence: 99%